Mulheres na educação profissional: movimentos dos cursos subsequentes do Colégio Técnico Industrial de Santa Maria - Dorneles, Thais da Silva (2020)
This research study was based on the Work and Education area, associated with the research field of Policies and Management in Professional and Technological Education of the Graduate Program of the Colégio Técnico Industrial de Santa Maria. This study aimed to analyze women's movements in their trajectory and perspectives after participating in courses at CTISM, in 2018 and 2019. The specific objectives were: 1) To contextualize the policies of Professional Education and the participation of women in the workforce; 2) To describe CTISM history and its offer of subsequent courses; 3) To understand the trajectory of entry, permanence, and perspectives for women’s participation in the workforce in subsequent technical courses at CTISM. This is a qualitative and exploratory research in which documentary and bibliographic data was analyzed. Data was collected from scientific journals in research portals and repositories, as well as by using semi-structured surveys, field journal; focus groups, and interviews. Data was analyzed using content analysis based on the following categories: research on women in professional education, who are the women attending subsequent technical courses at CTISM, what are the reasons for engaging, continuing, and their perspectives on the workforce and their perception of women at CTISM. Participants were women attending Subsequent Courses at CTISM whose entry was 2018 and 2019. The study recognizes the importance of the Professional Education policy to look at the trajectory of women in EPT courses, to reflect about the entry and permanence of women and to develop new research focusing on women in EPT. Most women who access subsequent courses at CTISM, are between 18 and 30 years old, single, have an average family income between 1 and 2 minimum wages, and have no children. Subsequent courses are essential in the trajectory of women, contributing to their training and to the workforce. Thus, the results of this research point to the importance of night courses and creation of support and monitoring networks for women attending CTISM Subsequent Courses.